Recent changes in housing policies and their distributional impact across Europe - Francesco Figari; Katarina Hollan; Manos Matsaganis; Eszter Zolyomi (University of Essex, Institute for Social and Economic Research (ISER), 2019)
This paper aims to explore how housing allowances and mortgage interest tax relief have evolved in recent years, against the background of falling disposable incomes and rising housing costs. The analysis focuses on seven EU countries (Greece, Italy, Austria, Hungary, the Netherlands, Sweden and the UK), covering a range of housing market developments and housing policy responses. The first part of the paper provides an overview of housing market trends over the period following the financial crisis and examines recent changes in housing policies in the countries concerned. The next part discusses the main features of two specific housing policy instruments, housing allowance and mortgage interest tax relief, also exploring recent changes there and the motives behind these. The last part estimates the distributional impact of housing allowances and mortgage tax relief in 2016 as compared with 2007 using the European tax-benefit model EUROMOD. The paper concludes with a discussion of the results and of the policy implications.
Keywords: H53; I32; I38; 330; social welfare; housing policies; housing allowances; tax reliefs; EUROMOD